Evaluation of orphan drug therapies and associated monitoring guidelines - Bhavadharini, Pandiarasu; A. Samath, Suhaina; Ali, Jabarulla Mohamed (International Journal of Basic & Clinical Pharmacology, 2024)
Orphan drugs, designed for the treatment and prevention of rare medical conditions known as orphan diseases, are infrequently accessible due to their high costs and limited research. The prevalence of rare diseases varies across countries based on population demographics. The Food and Drug Administration (FDA) has approved over 770 drugs with 77 designations for orphan status. Some of these drugs, often discovered by the pharmaceutical industry, are both highly valuable and expensive. When using orphan drugs, specific parameters need to be monitored. Therapeutic monitoring should align with the patient’s physical condition and the severity of the disease. This article aims to comprehensively examine the development of orphan drugs and their monitoring protocols.